Polyolefin foam beads and method for manufacturing the same
Patent Information
- Application Number
- KR1020237023127
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-14
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2040-12-14
Smart Images

Figure 112023074841610-PCT00006_ABST
Abstract
Description
Technology Field
[0001] The present disclosure relates to polyolefin foam beads and a method for manufacturing the same. The present disclosure further relates to an element manufactured from foam beads, a product comprising the element, and the use of foam beads in bead-filling applications. Background Technology
[0002] Polyolefin products, such as ENGAGE™ polyolefin elastomers (POE) and INFUSE™ olefin block copolymers (OBC), have various applications in industry. For example, in the footwear industry, components such as midsoles are traditionally manufactured from cross-linked EVA / POE and EVA / OBC foams produced through chemical foaming. However, this process is highly labor-intensive, and therefore, alternative foaming technologies with environmentally friendly and cost-saving processes are required.
[0003] Bead foaming technology, a type of physical foaming, offers options. Compared to chemical foaming, the advantages of bead foaming include the absence of unpleasant odors, less contamination of the mold, different visual and tactile perceptions, and isotropic properties of the part. Most importantly, the bead foaming process separates the foaming process from the molding process.
[0004] Typically, there are two types of commercial use of bead foams in the footwear industry, represented by Adidas Boost (TPU) and Nike Joyride, respectively. The former involves bead production and steam-chest molding, whereas the latter involves bead production and filling the voids with separate beads to form elements (e.g., midsoles). To ensure good sintering during steam-chest molding, the foam beads must not be crosslinked or may only be partially crosslinked with a relatively low gel content. For bead-filled applications (not only shoes but also other uses such as saddles, pillows, etc.), the foam beads can have relatively good elasticity because crosslinking is permitted.
[0005] There is still a demand for foamed beads with improved properties, such as elasticity.
[0006] In one embodiment, the present disclosure provides foam beads formed from a composition comprising one or more polyolefin copolymers, wherein the foam beads have a gel content of 80% or more and a tanδ of 0.11 or less at 1 rad / s.
[0007] In a further embodiment, the present disclosure provides a method for manufacturing polyolefin foam beads, and the method is,
[0008] (a) a step of providing a composition comprising one or more polyolefin copolymers;
[0009] (b) a step of pelletizing the composition to form pellets;
[0010] (c) a step of crosslinking the pellet to a gel content of 80% or more; and
[0011] (d) a step of foaming the cross-linked pellets into foam beads, and
[0012] Here, the foam beads have a tanδ of 0.11 or less at 1 rad / s.
[0013] In a further embodiment, the present disclosure provides an element made from a plurality of foam beads as described herein, comprising a cavity filled with foam beads.
[0014] In a further embodiment, the present disclosure provides a product comprising elements as described herein.
[0015] In a further embodiment, the present disclosure provides the use of foam beads as described herein in bead-filling applications.
[0016] Both the foregoing general description and the following detailed description are merely illustrative and descriptive and should be understood as not limiting the invention as claimed. Brief explanation of the drawing
[0017] Figure 1 is a graph showing the Tanδ of various foamed beads during frequency sweeping. Figure 2 is a scanning electron microscope (SEM) image of foamed beads prepared in the example. Specific details for implementing the invention
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention pertains. Additionally, all publications, patent applications, patents, and other references mentioned herein are incorporated by reference.
[0019] The following detailed description refers to the accompanying drawings, which illustrate specific details and embodiments in which the present invention may be practiced. Other embodiments may be utilized and variations may be made without departing from the scope of the present invention. Since some embodiments may be combined with one or more other embodiments to form new embodiments, the various embodiments are not necessarily mutually exclusive.
[0020] In the context of various embodiments, the articles "a," "an," and "the" used in relation to a feature or element include a reference to one or more features or elements. All scopes include an endpoint unless otherwise specified.
[0021] As disclosed herein, the terms “comprising,” “including,” “having,” and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether specifically disclosed. To avoid doubt, any composition claimed through the use of the term “comprising” may include any additional additives, adjuvants, or compounds, whether polymeric or not, unless otherwise stated. In contrast, the term “consisting essentially of” excludes any other components, steps, or procedures from the scope of subsequent references, except those that are not essential to operability. The term “consisting of” excludes components, steps, or procedures that are not specifically described or listed.
[0022] As disclosed herein, unless otherwise indicated, all percentages mentioned herein are by weight and temperatures are in °C.
[0023] A. Polyolefin foam beads
[0024] The present disclosure provides polyolefin copolymer foam beads. The foam beads are formed from a composition comprising one or more polyolefin copolymers.
[0025] In some embodiments, foam beads may be formed from a composition comprising one or more polyolefin copolymers and optionally, one or more additives.
[0026] In some specific embodiments, foam beads may be formed from a composition comprising one or more polyolefin copolymers, wherein at least 70 wt% of the one or more polyolefin copolymers is silane-grafted.
[0027] In some specific embodiments, foam beads may be formed from a composition comprising (A) one or more polyolefin copolymers and (B) one or more optional additives, wherein at least 70 wt% of the one or more polyolefin copolymers is silane-grafted.
[0028] i. Polyolefin copolymer
[0029] As used herein, the terms “polyolefin” or “olefin-based polymer” refer to a polymer comprising 50% by weight or most by weight of an olefin (e.g., ethylene or propylene) in a polymerized form (based on the weight of the polymer) and optionally comprising one or more comonomers.
[0030] The term “ethylene-based polymer” as used herein refers to a polymer comprising 50% by weight or most by weight of ethylene in a polymerized form (based on the weight of the polymer) and optionally comprising one or more comonomers.
[0031] As used herein, the term “polymer” refers to a polymeric compound prepared by polymerizing monomers of the same or different types. Accordingly, the idiom “polymer” includes the term “homogeneous polymer” (used to refer to a polymer prepared from only one type of monomer, with the understanding that trace impurities may be included in the polymer structure) and the term “hybrid polymer” as defined below. Trace impurities, such as catalyst residues, may be incorporated into and / or within the polymer. Typically, the polymer is stabilized by one or more stabilizers in very small amounts (“ppm”).
[0032] As used herein, the term "copolymer" refers to a polymer produced by the polymerization of at least two different types of monomers. Accordingly, the term copolymer includes the term copolymer (used to denote a polymer produced from two different types of monomers) and a polymer produced from more than two different types of monomers.
[0033] In some embodiments, the composition may comprise at least 80 wt%, or at least 85 wt%, or at least 90 wt%, or at least 95 wt%, or at least 98 wt%, or at least 99 wt%, or at least 100 wt% of a polyolefin copolymer based on the total weight of the composition or additionally based on the total weight of the foam beads. In some embodiments, the composition may comprise a polyolefin copolymer, at least 80 wt%, or at least 85 wt%, or at least 90 wt%, or at least 95 wt%, or at least 98 wt%, or at least 99 wt%, or at least 100 wt% of a polyolefin copolymer based on the total weight of the composition or additionally based on the total weight of the foam beads.
[0034] In one embodiment, the polyolefin copolymer may have a melt index (MI) of 30 g / 10 min or less, 20 g / 10 min or less, 10 g / 10 min or less, or 5 g / 10 min or less. In one embodiment, the polyolefin copolymer may have an MI within a numerical range obtained by combining any two of the following endpoints: 0.1 g / 10 min, 0.5 g / 10 min, 0.8 g / 10 min, 1.0 g / 10 min, 1.5 g / 10 min, 2.0 g / 10 min, 5 g / 10 min, 10 g / 10 min, 20 g / 10 min, and 30 g / 10 min. In one embodiment, the polyolefin copolymer may have an MI of 0.1 g / 10 min or 0.5 g / 10 min or 0.8 g / 10 min to 1.0 g / 10 min or 1.5 g / 10 min or 2.0 g / 10 min or 5 g / 10 min or 10 g / 10 min or 20 g / 10 min or up to 30 g / 10 min. In one embodiment, the polyolefin copolymer may have an MI of 0.1 g / 10 min to 30 g / 10 min, or 0.1 g / 10 min to 20 g / 10 min, or 0.1 g / 10 min to 10 g / 10 min, or 0.5 g / 10 min to 8 g / 10 min, or 1 g / 10 min to 5 g / 10 min.
[0035] In one embodiment, the polyolefin copolymer may have a density of 0.850 g / cm³ or more, 0.855 g / cm³ or more, 0.860 g / cm³ or more, 0.865 g / cm³ or more, or 0.870 g / cm³ or more. In one embodiment, the polyolefin copolymer may have a density within a numerical range obtained by combining any two of the following endpoints: 0.850 g / cm³, 0.855 g / cm³, 0.860 g / cm³, 0.865 g / cm³, 0.870 g / cm³, 0.875 g / cm³, 0.880 g / cm³, 0.885 g / cm³, 0.890 g / cm³, 0.895 g / cm³, 0.900 g / cm³, 0.905 g / cm³, and 0.910 g / cm³. In one embodiment, the polyolefin copolymer may have a density of 0.850 g / cm³ or 0.855 g / cm³ or 0.860 g / cm³ or 0.865 g / cm³ or 0.870 g / cm³ or 0.875 g / cm³ up to 0.880 g / cm³ or 0.885 g / cm³ or 0.890 g / cm³ or 0.895 g / cm³ or 0.900 g / cm³ or 0.905 g / cm³ or 0.910 g / cm³. In one embodiment, the polyolefin copolymer may have a density of 0.850 g / cm³ to 0.910 g / cm³, 0.855 g / cm³ to 0.910 g / cm³, 0.860 g / cm³ to 0.910 g / cm³, 0.865 g / cm³ to 0.905 g / cm³, or 0.870 g / cm³ to 0.905 g / cm³.
[0036] In one embodiment, the polyolefin copolymer may have a Shore A hardness of 30 or more, 35 or more, 40 or more, 45 or more, or 50 or more. In one embodiment, the polyolefin copolymer may have a Shore A hardness within a numerical range obtained by combining any two of the following endpoints: 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, and 90. In one embodiment, the polyolefin copolymer may have a Shore A hardness from 30 or 35 or 40 or 45 or 50 or 55, 60 or 65 or 70 or 75, to 80 or 85 or 90. In one embodiment, the polyolefin copolymer may have a Shore A hardness of 30 to 90, 35 to 90, 40 to 90, 45 to 90, 50 to 90, or 55 to 90.
[0037] In some embodiments, the polyolefin copolymer may be a polyolefin elastomer (POE). In some embodiments, the polyolefin copolymer may be selected from the group consisting of one or more ethylene / α-olefin multiblock copolymers, one or more ethylene / α-olefin random copolymers, and any combination thereof.
[0038] (1) Ethylene / α-olefin multiblock copolymer
[0039] In some embodiments, the polyolefin copolymer may comprise an ethylene / α-olefin multiblock copolymer. In some embodiments, the polyolefin copolymer comprises an ethylene / α-olefin multiblock copolymer, for example, ethylene in a polymerized form and one or more copolymers of C3-C 20 Ethylene / C3-C composed of α-olefin comonomers (and optional additives) 20It may comprise an α-olefin multiblock copolymer. Non-limiting examples of suitable α-olefins include 1-propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecylene, and 1-tetradecene. In some exemplary embodiments, the α-olefin is C3-C 10 It may be an α-olefin, for example, a C4-C8α-olefin. In an exemplary embodiment, the polyolefin copolymer may comprise an ethylene / octene multiblock copolymer. In an exemplary embodiment, the ethylene / octene multiblock copolymer is commercially available under the trade name INFUSE™ from The Dow Chemical Company, Midland, Michigan, USA.
[0040] As used herein, the terms “ethylene / α-olefin multiblock copolymer” or “olefin block copolymer” refer to a copolymer comprising ethylene and one or more copolymerizable α-olefin comonomers in a polymerized form, characterized by multiple blocks or segments of two or more (preferably three or more) polymerized monomer units (wherein the blocks or segments differ in chemical or physical properties). In particular, the term refers to a polymer comprising two or more (preferably three or more) chemically distinct regions or segments joined in a substantially linear manner, that is, a polymer comprising chemically differentiated units joined end-to-end (covalently bonded) to the polymerized functional groups instead of in a pendant or grafted manner. The above blocks differ in the amount or type of comonomer incorporated therein, density, amount of crystallinity, type of crystallinity (e.g., polyethylene versus polypropylene), crystallite size attributable to the polymer of such composition, type or degree of stereoregularity (isotactic or syndiotactic), positional regularity or positional irregularity, amount of branching including long-chain branching or over-branching, homogeneity, and / or any other chemical or physical properties. The block copolymers are characterized by a unique distribution of both polymer polydispersity (PDI or Mw / Mn) and block length distribution, for example, based on the effect of using a shuttling agent(s) in combination with a catalyst system. Non-limiting examples of the olefin block copolymer of the present disclosure as well as methods for producing the same are disclosed in U.S. Patents No. 7,858,706 B2, No. 8,198,374 B2, No. 8,318,864 B2, No. 8,609,779 B2, No. 8,710,143 B2, No. 8,785,551 B2 and No. 9,243,090 B2, all of which are incorporated herein by reference in their entirety.
[0041] For example, a multiblock copolymer can be represented by the following chemical formula: (AB)n In the above formula, n is at least 1, preferably an integer greater than 1, e.g., 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more. Here, "A" represents a hard block or segment and "B" represents a soft block or segment. Preferably, segments A and B are connected in a substantially linear manner, as opposed to a substantially branched or substantially star-shaped manner. In another embodiment, segments A and B are randomly distributed along the polymer chain. That is, for example, the block copolymer generally does not have a structure such as AAA-AA-BBB-BB. In yet another embodiment, the block copolymer generally does not have a third type of block or segment containing different comonomer(s). In yet another embodiment, block A and block B each have a monomer or comonomer distributed substantially randomly within the block. That is, neither Block A nor Block B contains two or more sub-segments (or sub-blocks), such as tip segments, of distinct composition having a composition substantially different from the rest of the block.
[0042] Generally, olefin block copolymers are produced via a chain shuttler process, such as that described in, for example, U.S. Patent No. 7,858,706 incorporated herein by reference. Some chain shuttlers and related information are described in columns 16, line 39 through 19, line 44. Some catalysts are described in columns 19, line 45 through 46, line 19, and some co-catalysts are described in columns 46, line 20 through 51, line 28. Some process features are described in columns 51, line 29 through 54, line 56. Also refer to: U.S. Patent No. 7,608,668; U.S. Patent No. 7,893,166; and U.S. Patent No. 7,947,793, as well as U.S. Patent Publication No. 2010 / 0197880. Also refer to U.S. Patent No. 9,243,173.
[0043] Preferably, ethylene comprises the majority mole fraction of the total ethylene / α-olefin multiblock copolymer, i.e., ethylene comprises at least 50 weight percent of the total ethylene / α-olefin multiblock copolymer. More preferably, ethylene comprises at least 60 weight percent, at least 70 weight percent, or at least 80 weight percent, and the substantial remainder of the total ethylene / α-olefin multiblock copolymer comprises a C4-C8α-olefin comonomer. Preferably, the C4-C8α-olefin comonomer may be selected from 1-butene, 1-hexene, and 1-octene. In one embodiment, the ethylene / α-olefin multiblock copolymer contains 50 weight percent or 60 weight percent or 65 weight percent to 80 weight percent or 85 weight percent or 90 weight percent of ethylene. For many ethylene / octene multiblock copolymers, the composition comprises an ethylene content of more than 80 weight% of the total ethylene / octene multiblock copolymer and an octene content of 10 weight% to 15 weight%, or 15 weight% to 20 weight% of the total ethylene / octene multiblock copolymer.
[0044] The ethylene / α-olefin multiblock copolymer comprises varying amounts of “hard” segments and “soft” segments. The “hard” segments are blocks of polymerized units in which ethylene is present in amounts of more than 90 wt%, or 95 wt%, or more than 95 wt%, or more than 98 wt%, and up to 100 wt% based on the weight of the polymer. That is, the comonomer content (content of monomers other than ethylene) in the hard segments is less than 10 wt%, or 5 wt%, or less than 5 wt%, or less than 2 wt% based on the weight of the polymer, and may be as low as 0. In some embodiments, the hard segments comprise all or substantially all units derived from ethylene. The “soft” segments are blocks of polymerized units in which the comonomer content (content of monomers other than ethylene) is greater than 5 wt%, or greater than 8 wt%, greater than 10 wt%, or greater than 15 wt% based on the weight of the polymer. In one embodiment, the comonomer content in the soft segment is greater than 20 wt%, or greater than 25 wt%, or greater than 30 wt%, or greater than 35 wt%, or greater than 40 wt%, or greater than 45 wt%, or greater than 50 wt%, or greater than 60 wt%, and may be up to 100 wt%.
[0045] Soft segments may be present in the ethylene / α-olefin multiblock copolymer in an amount ranging from 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, or 45 wt% to 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%, 95 wt%, or 99 wt% of the total weight of the ethylene / α-olefin multiblock copolymer. Conversely, hard segments may be present in a similar range. The weight percentages of the soft segments and the weight percentages of the hard segments may be calculated based on data obtained from DSC or NMR. Such methods and calculations are disclosed, for example, in U.S. Patent No. 7,608,668, the entire contents of which are incorporated herein by reference. In particular, the weight percentages of hard and soft segments and the comonomer content can be determined as described in columns 57 to 63 of U.S. Patent No. 7,608,668.
[0046] In one embodiment, the ethylene / α-olefin polyblock copolymer is manufactured by a continuous process and has a polydispersity index (Mw / Mn) of 1.7 to 3.5, or 1.8 to 3, or 1.8 to 2.5, or 1.8 to 2.2. When manufactured by a batch process or a semi-batch process, the ethylene / α-olefin polyblock copolymer has an Mw / Mn of 1.0 to 3.5, or 1.3 to 3, or 1.4 to 2.5, or 1.4 to 2.
[0047] Suitable ethylene / α-olefin multiblock copolymers are INFUSE from Dow TM , for example, it could be INFUSE™ D9130.05.
[0048] (2) Ethylene / α-olefin random copolymer
[0049] In some embodiments, the polyolefin copolymer may comprise an ethylene / α-olefin random copolymer. The ethylene / α-olefin random copolymer may be an ethylene / propylene random copolymer or an ethylene / C4-C8α-olefin random copolymer. In one embodiment, the ethylene / α-olefin copolymer may be an ethylene / C4-C8α-olefin copolymer. The ethylene / C4-C8α-olefin copolymer is composed of, or otherwise consists of, ethylene and one copolymerizable C4-C8α-olefin comonomer in a polymerized form. The C4-C8α-olefin comonomer may be selected from 1-butene, 1-hexene, and 1-octene.
[0050] Suitable ethylene / α-olefin random copolymers may be ENGAGE™ from Dow, e.g., ENGAGE™ 8150 or ENGAGE™ 7467.
[0051] ii Silane-grafted polyolefin copolymer
[0052] To form the foam beads described herein, at least some of the polyolefin copolymers included in the composition may be silane-grafted. That is, the composition may form a silane-grafted polyolefin copolymer formed using a silane monomer and a polyolefin copolymer as described and grafted thereon. In some exemplary embodiments, the silane-grafted polyolefin copolymer is a silane-grafted ethylene / C3-C 20 α-olefin multiblock copolymers, e.g., silane-grafted ethylene / C3-C 10 It may be an α-olefin multiblock copolymer. In another exemplary embodiment, the silane-grafted polyolefin copolymer may be a silane-grafted ethylene / α-olefin random copolymer, for example, a silane-grafted ethylene / C4-C8α-olefin random copolymer.
[0053] The "silane monomer" used to functionalize the polyolefin copolymer is a silane-containing monomer that can be grafted onto the polyolefin copolymer to form a silane-functionalized polyolefin copolymer and can crosslink the polyolefin copolymer. In some embodiments, the silane monomer may be a hydrolyzable silane monomer. Non-limiting examples of suitable hydrolyzable silane monomers include vinyltrimethoxysilane (VTMS), vinyltriethoxysilane (VTES), vinyltriacetoxysilane, and gamma-(meth)acryloxypropyltrimethoxysilane. In an exemplary embodiment, the hydrolyzable silane monomer may be VTMS.
[0054] Silane-grafted polyolefin copolymers can be formed by a process such as the Sioplas process, in which hydrolyzable silane monomers (e.g., vinyl silane monomers) are grafted onto the backbone of a polyolefin copolymer. The hydrolyzable silane monomers can be grafted onto the polyolefin copolymer using an amount of organic peroxide suitable for forming the silane-grafted polyolefin copolymer, such as 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane.
[0055] In some embodiments, the silane-grafted polyolefin copolymer may contain a silane grafting ratio of more than 0.3 wt%, more than 0.5 wt%, more than 0.6 wt%, more than 0.8 wt%, or more than 1.0 wt% based on the total weight of the silane-grafted polyolefin copolymer. In some embodiments, the silane-grafted polyolefin copolymer may comprise a silane grafting ratio based on the total weight of the silane-grafted polyolefin copolymer ranging from 0.1 wt% or 0.3 wt% or 0.5 wt% or 0.6 wt% or 0.8 wt% or 1.0 wt% to 1.1 wt% or 1.2 wt% or 1.5 wt% or 1.8 wt% or 2.0 wt% or 2.5 wt% or 3.0 wt% or 4.0 wt% or 5.0 wt%. In some embodiments, the silane-grafted polyolefin copolymer may comprise a silane grafting ratio of 0.1 wt% to 5.0 wt%, 0.3 wt% to 4.0 wt%, or 0.5 wt% to 3.0 wt% based on the total weight of the silane-grafted polyolefin copolymer. As used herein, the term “silane grafting ratio” refers to the ratio of the weight of the silane grafted onto the silane-grafted polyolefin copolymer to the total weight of the silane-grafted polyolefin copolymer.
[0056] In some embodiments, the foam beads may be formed from a composition comprising 70 wt% or more, 75 wt% or more, 80 wt% or more, 85 wt% or more, 90 wt% or more, 95 wt% or more, 98 wt% or more, 99 wt% or more, or 100 wt% of a silane-grafted polyolefin copolymer based on the total weight of the polyolefin copolymer(s) included in the composition. In some embodiments, foam beads may be formed from a composition comprising 70 wt% or 75 wt% or 80 wt% or 85 wt% to 90 wt% or 95 wt% or 98 wt% or 99 wt%, or 100 wt% of silane-grafted polyolefin copolymer based on the total weight of the polyolefin copolymer(s) included in the composition. In some embodiments, foam beads may be formed from a composition comprising 100 wt% of silane-grafted polyolefin copolymer based on the total weight of the polyolefin copolymer(s) included in the composition.
[0057] Silane-grafted polyolefin copolymers are useful for crosslinking by silane chemistry. It is understood that crosslinking can be performed by methods other than silane chemistry, for example, electron beam irradiation, gamma irradiation, or free radical chemistry-based crosslinking.
[0058] iii Non-silane-grafted polyolefin copolymer
[0059] A composition for forming foam beads comprising a silane-grafted polyolefin copolymer as described above may comprise a non-silane-grafted polyolefin copolymer. As used herein, "non-silane-grafted polyolefin copolymer" refers to one or more polyolefin copolymers included in the composition for forming foam beads in addition to the silane-grafted polyolefin copolymer as described above.
[0060] The non-silane-grafted polyolefin copolymer may comprise any polyolefin copolymer described herein that is not grafted with silane. The non-silane-grafted polyolefin copolymer is different from the silane-grafted polyolefin copolymer described above, because at least the non-silane-grafted polyolefin copolymer is not silane-functionalized or silane-grafted.
[0061] In the embodiments, the non-silane-grafted polyolefin copolymer and the polyolefin copolymer used to form the silane-grafted polyolefin copolymer may be physically and / or compositionally and / or structurally identical or different.
[0062] In some embodiments, the foam beads may be formed from a polymer comprising a non-silane-grafted polyolefin copolymer in an amount of 30 wt% or less, 25 wt% or less, 20 wt% or less, 15 wt% or less, 10 wt% or less, 5 wt% or less, 3 wt% or less, 2 wt% or less, or 1 wt% or less, or 0 wt% based on the total weight of the polyolefin copolymer(s) included in the composition. In some embodiments, foam beads may be formed from a composition comprising non-silane-grafted polyolefin copolymers ranging from 0 wt% or 1 wt% or 2 wt% or 3 wt% or 5 wt% to 10 wt% or 15 wt% or 20 wt% or 25 wt% or 30 wt%, based on the total weight of the polyolefin copolymer(s) included in the composition. In some embodiments, foam beads may be formed from a composition without non-silane-grafted polyolefin copolymers.
[0063] In some embodiments, the non-silane-grafted polyolefin copolymer may be an unmodified polyolefin copolymer. Examples of suitable unmodified polyolefin copolymers include ethylene or propylene random / block copolymers, such as INFUSE™, ENGAGE™, VERSIFY™, etc.
[0064] In some embodiments, the composition for forming foam beads may further comprise a polyolefin derivative, such as an ethylene vinyl acetate (EVA) copolymer with a high VA content (e.g., having a VA content of more than 18 wt% based on the total weight of EVA). Suitable examples of EVA copolymers include ELVAX® 460, ELVAX® 360, ELVAX® 265, ELVAX® 260, ELVAX® 250, and ELVAX® 40L-03.
[0065] iv. additives
[0066] The composition may include one or more optional additives. Non-limiting examples of suitable additives include nucleating agents, cell size stabilizers, antioxidants, colorants, inorganic fillers, flow aids, viscosity control agents, and combinations thereof.
[0067] In one embodiment, the foam beads are formed from a composition containing one or more optional additives in an amount ranging from 0 wt% or 0.01 wt% to 0.3 wt% or 0.5 wt% or 1 wt% or 2 wt% or 3 wt% or 5 wt% based on the total weight of the composition or additionally based on the total weight of the foam beads. In another embodiment, the foam beads are formed from a composition containing 0 wt% to 5 wt%, or 0 wt% to 1 wt%, or 0.01 wt% to 5 wt% based on the total weight of the composition or additionally based on the total weight of the foam beads.
[0068] v. Foam beads
[0069] The foam beads of the present application may be formed from a composition comprising one or more polyolefin copolymers and optionally, one or more additives. In some embodiments, the foam beads may be formed from a composition comprising 80 wt% or 85 wt%, 90 wt%, 95 wt%, 98 wt%, 99 wt%, or 100 wt% of a polyolefin copolymer as described herein, based on the total weight of the composition or additionally based on the total weight of the foam beads, and one or more optional additives based on the total weight of the composition or additionally based on the total weight of the foam beads, in an amount ranging from 0 wt% or 0.01 wt% to 0.3 wt% or 0.5 wt% or 1 wt% or 2 wt% or 3 wt% or 5 wt%.
[0070] In some specific embodiments, the foam beads of the present application may be formed from a composition comprising one or more polyolefin copolymers, wherein at least 70 wt% of the one or more polyolefin copolymers is silane-grafted.
[0071] In some embodiments, the composition may optionally include one or more optional additives.
[0072] In some embodiments, the foam beads
[0073] (A) 80 wt% or 85 wt% or 90 wt% to 95 wt% or 98 wt% or 99 wt% or 100 wt% based on the total weight of the composition, or additionally based on the total weight of the foam beads; and
[0074] (B) Optionally, based on the total weight of the composition, or additionally based on the total weight of the foam beads, it may include one or more optional additives ranging from 0 wt% or 0.01 wt% to 0.3 wt% or 0.5 wt% or 1 wt% or 2 wt% or 3 wt% or 5 wt%;
[0075] Herein, one or more polyolefin copolymers comprise one or more silane-grafted polyolefin copolymers in an amount ranging from 70 wt% or 75 wt% or 80 wt% or 85 wt%, up to 90 wt% or 95 wt% or 98 wt% or 99 wt%, or up to 100 wt% based on the total weight of the polyolefin copolymer(s) included in the composition; and one or more non-silane-grafted polyolefin copolymers in an amount ranging from 0 wt% or 1 wt% or 2 wt% or 3 wt% or 5 wt%, up to 10 wt% or 15 wt% or 20 wt% or 25 wt% or 30 wt% based on the total weight of the polyolefin copolymer(s) included in the composition.
[0076] In some embodiments, the foam beads may have a gel content of 80% or more, 85% or more, or 90% or more. In some embodiments, the foam beads may have a gel content of 80% or 85% to 90% or 95% or 98% or 99%, or 100%.
[0077] In some embodiments, foam beads may be formed from pellets of the composition as described herein. In some embodiments, foam beads may be formed from cross-linked pellets of the composition as described herein. In some embodiments, the cross-linked pellets of the composition may have a gel content of 80% or more, 85% or more, or 90% or more. In some embodiments, the cross-linked pellets may have a gel content of 80% or 85% to 90% or 95% or 98% or 99%, or 100%. In some embodiments, foam beads are formed from the composition as described above by cross-linking the pellets of the composition before foaming the pellets. In some embodiments, foam beads are formed by foaming the cross-linked pellets of the composition as described above.
[0078] In some embodiments, the foam beads may have a foam density of less than 0.20 g / cc. In some embodiments, the foam beads have a foam density of 0.06 g / cc or 0.07 g / cc or 0.08 g / cc or 0.09 g / cc or 0.10 g / cc or 0.11 g / cc or 0.12 g / cc or 0.13 g / cc up to 0.14 g / cc or 0.15 g / cc or 0.16 g / cc or 0.17 g / cc or 0.18 g / cc or 0.19 g / cc or 0.20 g / cc. In some embodiments, the foam beads may have a foam density of 0.06 g / cc to 0.20 g / cc, 0.08 g / cc to 0.18 g / cc, 0.10 g / cc to 0.17 g / cc, or 0.12 g / cc to 0.16 g / cc.
[0079] In some embodiments, the foam beads may have a tanδ at 0.1 rad / s of 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, or 0.12 or less. In some embodiments, the foam beads may have a tanδ at 1 rad / s of 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, or 0.10 or less. In some embodiments, the foam beads may have a tanδ at 10 rad / s of 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, or 0.08 or less.
[0080] In some embodiments, the foam beads may have an average cell size of less than about 100 μm. In some embodiments, the foam beads may have an average cell size ranging from about 10 μm, about 15 μm, about 20 μm, up to 80 μm, or 85 μm, or 90 μm, or 95 μm, or 100 μm.
[0081] In some embodiments, foam beads may be manufactured by using a method for manufacturing polyolefin foam beads as described below.
[0082] B. Method for manufacturing polyolefin foam beads
[0083] The present disclosure provides a method for manufacturing polyolefin foam beads, and the method is,
[0084] (a) a step of providing a composition comprising one or more polyolefin copolymers;
[0085] (b) a step of pelletizing the composition to form pellets;
[0086] (c) a step of crosslinking the pellet to a gel content of 80% or more; and
[0087] (d) a step of foaming the cross-linked pellets into foam beads, and
[0088] Here, the foam beads have a tanδ of 0.11 or less at 1 rad / s.
[0089] i. Polyolefin composition
[0090] A method for manufacturing polyolefin foam beads as described herein comprises (a) the step of providing a composition comprising one or more polyolefin copolymers, wherein the composition may also be referred to herein as "composition" or "polyolefin composition."
[0091] In some embodiments, the composition provided herein may comprise one or more polyolefin copolymers (e.g., one or more of those described in the “polyolefin foam beads” portion), and optionally, one or more additives.
[0092] In some embodiments, the composition may comprise a polyolefin copolymer in an amount of 80 wt%, or 85 wt%, or 90 wt%, to 95 wt%, or 98 wt%, or 99 wt%, or 100 wt%, based on the total weight of the composition. In some embodiments, the composition may comprise a polyolefin copolymer in an amount of 80 wt%, or 85 wt%, or 90 wt%, or from 95 wt%, or from 98 wt%, or from 99 wt%, or 100 wt%, based on the total weight of the composition.
[0093] In one embodiment, the polyolefin copolymer may have a melt index (MI) of 30 g / 10 min or less, 20 g / 10 min or less, 10 g / 10 min or less, or 5 g / 10 min or less. In one embodiment, the polyolefin copolymer may have an MI within a numerical range obtained by combining any two of the following endpoints: 0.1 g / 10 min, 0.5 g / 10 min, 0.8 g / 10 min, 1.0 g / 10 min, 1.5 g / 10 min, 2.0 g / 10 min, 5 g / 10 min, 10 g / 10 min, 20 g / 10 min, and 30 g / 10 min. In one embodiment, the polyolefin copolymer may have an MI of 0.1 g / 10 min or 0.5 g / 10 min or 0.8 g / 10 min to 1.0 g / 10 min or 1.5 g / 10 min or 2.0 g / 10 min or 5 g / 10 min or 10 g / 10 min or 20 g / 10 min or up to 30 g / 10 min. In one embodiment, the polyolefin copolymer may have an MI of 0.1 g / 10 min to 30 g / 10 min, or 0.1 g / 10 min to 20 g / 10 min, or 0.1 g / 10 min to 10 g / 10 min, or 0.5 g / 10 min to 8 g / 10 min, or 1 g / 10 min to 5 g / 10 min.
[0094] In one embodiment, the polyolefin copolymer may have a density of 0.850 g / cm³ or more, 0.855 g / cm³ or more, 0.860 g / cm³ or more, 0.865 g / cm³ or more, or 0.870 g / cm³ or more. In one embodiment, the polyolefin copolymer may have a density within a numerical range obtained by combining any two of the following endpoints: 0.850 g / cm³, 0.855 g / cm³, 0.860 g / cm³, 0.865 g / cm³, 0.870 g / cm³, 0.875 g / cm³, 0.880 g / cm³, 0.885 g / cm³, 0.890 g / cm³, 0.895 g / cm³, 0.900 g / cm³, 0.905 g / cm³, and 0.910 g / cm³. In one embodiment, the polyolefin copolymer may have a density of 0.850 g / cm³ or 0.855 g / cm³ or 0.860 g / cm³ or 0.865 g / cm³ or 0.870 g / cm³ or 0.875 g / cm³ up to 0.880 g / cm³ or 0.885 g / cm³ or 0.890 g / cm³ or 0.895 g / cm³ or 0.900 g / cm³ or 0.905 g / cm³ or 0.910 g / cm³. In one embodiment, the polyolefin copolymer may have a density of 0.850 g / cm³ to 0.910 g / cm³, 0.855 g / cm³ to 0.910 g / cm³, 0.860 g / cm³ to 0.910 g / cm³, 0.865 g / cm³ to 0.905 g / cm³, or 0.870 g / cm³ to 0.905 g / cm³.
[0095] In one embodiment, the polyolefin copolymer may have a Shore A hardness of 30 or more, 35 or more, 40 or more, 45 or more, or 50 or more. In one embodiment, the polyolefin copolymer may have a Shore A hardness within a numerical range obtained by combining any two of the following endpoints: 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, and 90. In one embodiment, the polyolefin copolymer may have a Shore A hardness from 30 or 35 or 40 or 45 or 50 or 55, 60 or 65 or 70 or 75, to 80 or 85 or 90. In one embodiment, the polyolefin copolymer may have a Shore A hardness of 30 to 90, 35 to 90, 40 to 90, 45 to 90, 50 to 90, or 55 to 90.
[0096] In some embodiments, the polyolefin copolymer may be a polyolefin elastomer (POE). In some embodiments, the polyolefin copolymer may be selected from the group consisting of ethylene / α-olefin multiblock copolymers, ethylene / α-olefin random copolymers, and combinations thereof.
[0097] In some embodiments, the polyolefin copolymer may comprise an ethylene / α-olefin multiblock copolymer. In some embodiments, the polyolefin copolymer comprises an ethylene / α-olefin multiblock copolymer, for example, ethylene in a polymerized form and one or more copolymers of C3-C 20 Ethylene / C3-C composed of α-olefin comonomers (and optional additives) 20It may comprise an α-olefin multiblock copolymer. Non-limiting examples of suitable α-olefins include 1-propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecylene, and 1-tetradecene. In some exemplary embodiments, the α-olefin is C3-C 10 It may be an α-olefin, for example, a C4-C8α-olefin. In an exemplary embodiment, the polyolefin copolymer may comprise an ethylene / octene multiblock copolymer. In an exemplary embodiment, the ethylene / octene multiblock copolymer is commercially available from DOW under the trade name INFUSE™.
[0098] A suitable ethylene / α-olefin multiblock copolymer may be INFUSE™ from Dow, e.g., INFUSE™ D9130.05.
[0099] In some embodiments, the polyolefin copolymer may comprise an ethylene / α-olefin random copolymer. The ethylene / α-olefin random copolymer may be an ethylene / propylene random copolymer or an ethylene / C4-C8α-olefin random copolymer. In one embodiment, the ethylene / α-olefin copolymer may be an ethylene / C4-C8α-olefin copolymer. The ethylene / C4-C8α-olefin copolymer is composed of, or otherwise consists of, ethylene and one copolymerizable C4-C8α-olefin comonomer in a polymerized form. The C4-C8α-olefin comonomer may be selected from 1-butene, 1-hexene, and 1-octene.
[0100] Suitable ethylene / α-olefin random copolymers may be ENGAGE™ from Dow, e.g., ENGAGE™ 8150 or ENGAGE™ 7467.
[0101] In some embodiments, the compositions provided herein may optionally include one or more additives. Non-limiting examples of suitable additives include nucleating agents, cell size stabilizers, antioxidants, coloring agents, inorganic fillers, flow aids, viscosity control agents, and combinations thereof.
[0102] In one embodiment, the composition may include one or more optional additives in an amount ranging from 0 wt% or 0.01 wt% to 0.3 wt% or 0.5 wt% or 1 wt% or 2 wt% or 3 wt% or 5 wt% based on the total weight of the composition. In another embodiment, the composition may include optional additives in an amount ranging from 0 wt% to 5 wt%, or from 0 wt% to 1 wt%, or from 0.01 wt% to 5 wt% based on the total weight of the composition.
[0103] In some embodiments, the composition may comprise a polyolefin copolymer as described herein in an amount of 80 wt% or 85 wt% or 90 wt%, up to 95 wt% or 98 wt% or 99 wt%, or 100 wt% based on the total weight of the composition, and one or more optional additives in an amount of 0 wt% or 0.01 wt%, up to 0.3 wt% or 0.5 wt% or 1 wt% or 2 wt% or 3 wt% or 5 wt% based on the total weight of the composition.
[0104] In some specific embodiments, the composition provided herein may comprise one or more polyolefin copolymers, wherein at least 70 wt% of the one or more polyolefin copolymers is silane-grafted.
[0105] In some specific embodiments, the composition provided herein may optionally include one or more optional additives.
[0106] In some embodiments, the composition may comprise a silane-grafted polyolefin copolymer. The silane-grafted polyolefin copolymer may comprise any polyolefin copolymer as described herein that is further functionalized or grafted with a silane monomer.
[0107] In some exemplary embodiments, the silane-grafted polyolefin copolymer is a silane monomer and a grafted ethylene / C3-C 20 α-olefin multiblock copolymer, i.e., silane-grafted ethylene / C3-C 20 α-olefin multiblock copolymers, e.g., silane-grafted ethylene / C3-C 10 It may be an α-olefin multiblock copolymer. In another exemplary embodiment, the silane-grafted polyolefin copolymer may be an ethylene / α-olefin random copolymer as described, grafted with a silane monomer, i.e., a silane-grafted ethylene / α-olefin random copolymer, for example, a silane-grafted ethylene / C4-C8α-olefin random copolymer. In some embodiments, the silane monomer may be a hydrolyzable silane monomer. Non-limiting examples of suitable hydrolyzable silane monomers include vinyltrimethoxysilane (VTMS), vinyltriethoxysilane (VTES), vinyltriacetoxysilane, and gamma-(meth)acryloxypropyltrimethoxysilane. In an exemplary embodiment, the hydrolyzable silane monomer may be VTMS.
[0108] Silane-grafted polyolefin copolymers can be formed by a process such as the Sioplas process, in which hydrolyzable silane monomers (e.g., vinyl silane monomers) are grafted onto the backbone of a polyolefin copolymer. The hydrolyzable silane monomers can be grafted onto the polyolefin copolymer using an amount of organic peroxide suitable for forming the silane-grafted polyolefin copolymer, such as 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane.
[0109] In some embodiments, the silane-grafted polyolefin copolymer may contain a silane grafting ratio of more than 0.3 wt%, more than 0.5 wt%, more than 0.6 wt%, more than 0.8 wt%, or more than 1.0 wt% based on the total weight of the silane-grafted polyolefin copolymer. In some embodiments, the silane-grafted polyolefin copolymer may comprise a silane grafting ratio based on the total weight of the silane-grafted polyolefin copolymer ranging from 0.1 wt% or 0.3 wt% or 0.5 wt% or 0.6 wt% or 0.8 wt% or 1.0 wt% to 1.1 wt% or 1.2 wt% or 1.5 wt% or 1.8 wt% or 2.0 wt% or 2.5 wt% or 3.0 wt% or 4.0 wt% or 5.0 wt%. In some embodiments, the silane-grafted polyolefin copolymer may contain a silane grafting ratio of 0.1 wt% to 5.0 wt%, 0.3 wt% to 4.0 wt%, or 0.5 wt% to 3.0 wt% based on the total weight of the silane-grafted polyolefin copolymer.
[0110] In one embodiment, the composition may comprise 70 wt% or more, 75 wt% or more, 80 wt% or more, 85 wt% or more, 90 wt% or more, 95 wt% or more, 98 wt% or more, 99 wt% or more, or 100 wt% of silane-grafted polyolefin copolymer based on the total weight of the polyolefin copolymer(s) included in the composition. In one embodiment, the composition may comprise 70 wt% or 75 wt% or 80 wt% or 85 wt% to 90 wt% or 95 wt% or 98 wt% or 99 wt%, or 100 wt% of silane-grafted polyolefin copolymer based on the total weight of the polyolefin copolymer(s) included in the composition. In one embodiment, the composition may comprise 100 wt% of a silane-grafted polyolefin copolymer based on the total weight of the polyolefin copolymer(s) included in the composition.
[0111] In some embodiments, the composition may include a non-silane-grafted polyolefin copolymer.
[0112] The non-silane-grafted polyolefin copolymer may comprise any polyolefin copolymer described herein that is not grafted with silane. The non-silane-grafted polyolefin copolymer is different from the silane-grafted polyolefin copolymer described above, because at least the non-silane-grafted polyolefin copolymer is not silane-functionalized or silane-grafted.
[0113] In the embodiments, the non-silane-grafted polyolefin copolymer and the polyolefin copolymer used to form the silane-grafted polyolefin copolymer may be physically and / or compositionally and / or structurally identical or different.
[0114] In one embodiment, the composition may comprise a non-silane-grafted polyolefin copolymer in an amount of 30 wt% or less, 25 wt% or less, 20 wt% or less, 15 wt% or less, 10 wt% or less, 5 wt% or less, 3 wt% or less, 2 wt% or less, or 1 wt% or less, or 0 wt%, based on the total weight of the polyolefin copolymer(s) included in the composition. In one embodiment, the composition may comprise a composition comprising a non-silane-grafted polyolefin copolymer in an amount ranging from 0 wt% or 1 wt% or 2 wt% or 3 wt% or 5 wt% to 10 wt% or 15 wt% or 20 wt% or 25 wt% or 30 wt%, based on the total weight of the polyolefin copolymer(s) included in the composition. In one embodiment, the composition may not contain a non-silane-grafted polyolefin copolymer.
[0115] In some embodiments, the non-silane-grafted polyolefin copolymer may be an unmodified polyolefin copolymer. Examples of suitable unmodified polyolefin copolymers include ethylene or propylene random / block copolymers, such as INFUSE™, ENGAGE™, VERSIFY™, etc.
[0116] In some embodiments, the composition for forming foam beads may further comprise a polyolefin derivative, such as an ethylene vinyl acetate (EVA) copolymer with a high VA content (e.g., having a VA content of more than 18 wt% based on the total weight of EVA). Suitable examples of EVA copolymers include ELVAX® 460, ELVAX® 360, ELVAX® 265, ELVAX® 260, ELVAX® 250, and ELVAX® 40L-03.
[0117] In some embodiments, the composition may include one or more optional additives. One or more additives optionally included in the composition may be those described above.
[0118] In some embodiments, the composition is,
[0119] (A) one or more polyolefin copolymers in an amount ranging from 80 wt% or 85 wt% or 90 wt%, up to 95 wt% or 98 wt% or 99 wt%, or 100 wt%, based on the total weight of the composition or additionally based on the total weight of the foam beads; and
[0120] (B) Optionally, based on the total weight of the composition, or additionally based on the total weight of the foam beads, it may include one or more optional additives ranging from 0 wt% or 0.01 wt% to 0.3 wt% or 0.5 wt% or 1 wt% or 2 wt% or 3 wt% or 5 wt%;
[0121] Herein, one or more polyolefin copolymers comprise one or more silane-grafted polyolefin copolymers in an amount ranging from 70 wt% or 75 wt% or 80 wt% or 85 wt%, up to 90 wt% or 95 wt% or 98 wt% or 99 wt%, or up to 100 wt% based on the total weight of the polyolefin copolymer(s) included in the composition; and one or more non-silane-grafted polyolefin copolymers in an amount ranging from 0 wt% or 1 wt% or 2 wt% or 3 wt% or 5 wt%, up to 10 wt% or 15 wt% or 20 wt% or 25 wt% or 30 wt% based on the total weight of the polyolefin copolymer(s) included in the composition.
[0122] ii. pelletization
[0123] A method for manufacturing polyolefin foam beads as described herein includes (b) a step of pelletizing a composition to form pellets.
[0124] In some embodiments, the pellet (also referred to herein as "micro-pellet") may be substantially spherical. In some embodiments, the pellet may have a diameter of 1.8 mm or 2.0 mm or 2.3 mm up to 3.0 mm or 3.5 mm or 3.8 mm. In certain embodiments, the pellet may have a diameter of 2.3 mm to 3.0 mm.
[0125] In some embodiments, pelletization may be performed by using a pelletizer to produce pellets of the composition. In some embodiments, pelletization may be performed by underwater pelletization. Generally, underwater pelletization may be performed by using an underwater pelletizer having a die plate generally equipped with a plurality of porous systems having a plurality of holes.
[0126] iii. Bridge
[0127] A method for manufacturing polyolefin foam beads as described herein includes (c) a step of crosslinking pellets.
[0128] In the method of the present disclosure, the crosslinking step is performed prior to the foaming step.
[0129] In some embodiments, crosslinking is performed up to a gel content of about 80% or more, about 85% or more, or about 90% or more. In some embodiments, crosslinking may be performed from about 80% or about 85% to about 90% or about 95% or about 98% or about 99%, or up to a gel content of about 100%.
[0130] In some embodiments, crosslinking may be performed by a method using silane chemistry, electron beam irradiation, gamma irradiation, or free radical chemistry-based crosslinking. In certain embodiments, crosslinking may be performed by using silane chemistry, i.e., silane crosslinking.
[0131] In some embodiments, a crosslinking agent may be used to crosslink pellets of the composition. The crosslinking agent is not particularly limited as long as the crosslinking can crosslink the copolymer. The crosslinking agent used may be a known organic peroxide used to crosslink polyethylene-based resins. Examples include percumyl-based compounds, e.g., dicumyl peroxide and tert-butylcumyl peroxide; perbutyl-based compounds, e.g., 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and di-tert-butyl peroxide; perhexyl-based compounds, e.g., tert-hexyl peroxybenzoate; and perocta-based compounds, e.g., 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate. These compounds may be used alone or as a combination of two or more classes thereof. In some exemplary embodiments, the lower limit of the amount of one or more crosslinking agents mixed may be about 0.05 parts by weight, about 0.1 parts by weight, about 0.2 parts by weight, about 0.3 parts by weight, about 0.4 parts by weight, or about 0.5 parts by weight per 100 parts by weight of the total weight of the polymer. The upper limit of the amount of one or more crosslinking agents mixed may be about 5.0 parts by weight, about 4.5 parts by weight, about 4.0 parts by weight, about 3.5 parts by weight, about 3.0 parts by weight, or about 2.5 parts by weight per 100 parts by weight of the total weight of the polymer.
[0132] In some embodiments, the crosslinking agent may be carried out at a temperature of about 20°C or about 40°C or about 60°C or about 80°C or about 100°C to about 120°C or about 150°C or about 180°C or about 200°C or about 220°C.
[0133] In some embodiments, the crosslinking agent may be carried out by radiation at a dose of, for example, 30 KGy to 80 KGy, 40 KGy to 70 KGy, or 45 KGy to 60 KGy.
[0134] In an exemplary embodiment in which silane crosslinking is utilized, crosslinking may be performed by the steps of soaking a pellet of a composition comprising a silane-grafted polyolefin copolymer with a catalyst (e.g., dibutyltin dilaurate) or a silane solution thereof, and exposing the pellet to air for wet crosslinking of the silane moiety.
[0135] In another exemplary embodiment in which silane crosslinking is utilized, crosslinking can be performed by immersing pellets of a composition comprising a silane-grafted polyolefin copolymer in hot water (e.g., at a temperature above 80°C) for wet crosslinking of the silane moiety.
[0136] iv. firing
[0137] A method for manufacturing polyolefin foam beads as described herein includes (d) a step of foaming cross-linked pellets into foam beads.
[0138] In the method of the present disclosure, the foaming step is performed after the crosslinking step.
[0139] In some embodiments, the foaming may be physical foaming.
[0140] In some embodiments, a blowing agent may be used to foam the cross-linked pellets. The blowing agent used for foaming is not particularly limited as long as the blowing agent can expand the cross-linked particles. Examples of blowing agents include inorganic physical blowing agents, e.g., air, nitrogen, carbon dioxide, argon, helium, oxygen, and neon, and organic physical blowing agents, e.g., aliphatic hydrocarbons, e.g., propane, n-butane, isobutane, n-pentane, isopentane, and n-hexane, alicyclic hydrocarbons, e.g., cyclohexane and cyclopentane, halogenated hydrocarbons, e.g., chlorofluoromethane, trifluoromethane, 1,1-difluoroethane, 1,1,1,2-tetrafluoroethane, methyl chloride, ethyl chloride, and methylene chloride, and dialkyl ethers, e.g., dimethyl ether, diethyl ether, and methyl ethyl ether. Among these, inorganic physical blowing agents are preferred because they do not deplete the ozone layer and are low-cost, and nitrogen, air, and carbon dioxide are particularly preferred. The blowing agent may be used alone or as a combination of two or more of these classes. In some embodiments, the amount of blowing agent used may be determined by taking into account the apparent density of the foamed beads to be desired, the type of multiblock copolymer, the type of blowing agent, etc., and is generally about 2 to about 20 parts by weight for organic physical blowing agents and about 0.5 to about 20 parts by weight for inorganic physical blowing agents per 100 parts by weight of the total weight of the polymer.
[0141] In some embodiments, foaming may be performed at a temperature around the melting temperature of the polymer. In some embodiments, foaming may be performed at a temperature from about 70°C or about 80°C or about 90°C or about 100°C to about 110°C or about 120°C or about 130°C or about 140°C or about 150°C.
[0142] In some embodiments, foaming may be performed at pressures ranging from about 10 Bar or about 20 Bar or about 30 Bar or about 40 Bar or about 50 Bar or about 60 Bar to about 100 Bar or about 120 Bar or about 150 Bar or about 180 Bar or about 200 Bar or about 220 Bar. In exemplary embodiments, foaming may be performed at pressures ranging from about 50 Bar to about 200 Bar.
[0143] In some embodiments, the foamed beads can be conditioned (e.g., at room temperature) to allow gas exchange between the inside and outside of the beads.
[0144] In some embodiments, the foam beads may have an average cell size of less than about 100 μm. In some embodiments, the foam beads may have an average cell size ranging from about 10 μm, about 15 μm, about 20 μm, up to 80 μm, or 85 μm, or 90 μm, or 95 μm, or 100 μm.
[0145] It was unexpectedly discovered that crosslinking prior to foaming improves elasticity. When crosslinking is performed prior to bead foaming (i.e., crosslinking of micro-pellets before foaming, "Pre-XL"), the energy loss of the resulting foamed beads (characterized by the tanδ of the dynamic mechanical analysis (DMA) of the resulting foamed beads) can be significantly reduced compared to the post-crosslinking approach (i.e., crosslinking of the foamed beads, "Post-XL"). In other words, Pre-XL can be a factor in significantly improving elasticity. This is particularly true when these Pre-XL bead foams have a gel content of over 80%, especially over 90%. These highly crosslinked and highly elastic bead foams may find promising potential uses in bead-filling applications.
[0146] C. Foam bead filling elements and products
[0147] The present disclosure further provides an element manufactured from foam beads as described herein.
[0148] In some embodiments, the element may be a foam bead-filled element. In some embodiments, the element may include a void filled with foam beads as described. In some embodiments, the element may be manufactured from foam beads as described through a bead-filling application. In some embodiments, the element may be manufactured by (i) filling the void with foam beads as described through a bead-filling port of the void, and (ii) closing all openings of the void, including, for example, the bead-filling port of the void. In some embodiments, the void may be a molded void. In some embodiments, the void may have a predetermined shape. In some embodiments, the void may be made of inorganic and / or organic materials, including fabric, polymer, leather, rubber, fiber, etc.
[0149] The present disclosure further provides a product comprising elements as described herein. In some embodiments, the product may comprise a foam bead filler element as a component. Examples of the product may include, but are not limited to, products for use in automotive parts, footwear components (e.g., midsoles), molded articles (e.g., toys or other household items), building materials, etc.
[0150] The present disclosure further provides uses for foam beads as described herein in bead-filling applications.
[0151] Examples
[0152] Some embodiments of the present invention will now be described in the following examples, where all parts and percentages are by weight unless otherwise specified.
[0153] raw materials
[0154] INFUSE™ D9130.05: Olefin block copolymer (ethylene / octene polyblock copolymer), density 0.886 g / cm³ (ASTM D792), MI 1.5 g / 10 min (ASTM D1238, at 190°C / 2.16 kg), Shore A = 80 (ASTM D2240).
[0155] Luperox 101 peroxide: 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane from Arkema.
[0156] XIAMETER OFS-6300: Vinyltrimethoxysilanes (VTMS) from Dow Corning.
[0157] DBTDL: Dibutyltin dilaurate, a silane wet curing catalyst from Sinopharm Chemical Reagent Co., Ltd.
[0158] n-Octyltriethoxysilane: Solvent of DBTDL from Sinopharm Chemical Reagent Co., Ltd.
[0159] Sample manufacturing
[0160] Preparation of silane-g-OBC pellets
[0161] Silane-grafted INFUSE™ D9130.05 was manufactured in a 40 mm diameter, 48 L / D 12-barrel ZSK-40 Coperion twin-screw extruder. The line was equipped with a 135 kW motor and had a maximum speed of 1,200 revolutions per minute (RPM). INFUSE™ D9130.05 was fed into the twin-screw extruder by loss from a weight feeder. To prevent polymer oxidation, nitrogen was supplied from the second barrel during the blending process to sweep oxygen from the system. The melt release temperature was measured using a portable thermocouple placed directly in the melt stream (the barrel set temperatures from the hopper to the die were 23 / 60 / 60 / 60 / 190 / 230 / 230 / 230 / 190 / 190 / 180°C). A mixture of silane (XIAMETER OFS-6300) and peroxide (LUPEROX 101) was formed and injected from barrel 6 into an extruder via a liquid pump.
[0162] To minimize the concentration of volatile components and residual silane in the melt, a vacuum system was used to remove residual volatile components from the melt in barrel 11 during the process. A vacuum of 0.065 to 0.070 MPa was used.
[0163] An underwater pelletizer with a 16-hole die was used to produce the blended pellets. Twelve of the 16 holes were plugged to inhibit the formation of pellet "chains" during pelletization. A 6-blade pelletizing hub was used.
[0164] The obtained OBC had varying grafted silane levels (0.36 to 2.93 wt%) based on the total weight of the silane-grafted ethylene / octene multiblock copolymer when measured using Fourier transform infrared spectroscopy (FTIR) according to the literature [Chuanmei Jiao et al., Silane Grafting and Crosslinking of Ethylene-Octene Copolymer, 41 European Polymer J. 1204 (2005)], the full contents of which are incorporated herein by reference. Table 1 lists information on the silane-grafted resin.
[0165] [Table 1]
[0166]
[0167] Crosslinking of silane-g-OBC pellets and foamed beads
[0168] Pre-crosslinking of silane-grafted OBC micro-pellets was performed in two ways:
[0169] (1) The pellet was immersed at room temperature with a catalyst solution of DBTDL in the solvent n-octyltriethoxysilane (DBTDL / n-octyltriethoxysilane = 3 / 10). 0.65 wt% of this catalyst solution (based on the weight of the pellet) was placed in a sealable fluoroplastic bottle, and then the weighed silane-grafted OBC micro-pellet was added. To ensure uniform distribution of the additive to the pellet and complete immersion, the bottle was first rolled for 1 minute and then placed on a movable roller (model number 88881004, Thermo Scientific) for further homogenization. After immersion, the immersed pellet was exposed to air for 7 days for wet crosslinking to ensure complete crosslinking of the silane moiety.
[0170] (2) Silane-grafted OBC micro-pellets were immersed in 85°C water for several days for wet crosslinking. The gel content was controlled by controlling the immersion time. After reaching the desired gel content, the immersion crosslinking was stopped.
[0171] Post-XL of the foamed beads was performed by method (1).
[0172] Manufacture of foam beads via autoclave batch foaming
[0173] Micro-pellets were fed into an autoclave equipped with a heating unit and a gas injection valve. The autoclave was heated to approximately the polymer melting temperature. Simultaneously, a blowing agent (in this case, high-pressure CO2) was injected into the clave for saturation (0.5 to 2 hours). The autoclave pressure will vary depending on the polymer type. A typical range is approximately 50 to 200 bar. After saturating the polymer with CO2 gas, rapid depressurization was applied to produce foam beads. The produced foam beads were conditioned at room temperature for several days to allow gas exchange between the inside and outside of the beads.
[0174] Performance measurement
[0175] (1) Gel content
[0176] The gel content was obtained in the following manner. Specimens of pellets or beads were placed in a 120-mesh metal mesh bag and boiled in 600 ml of xylene for 5 hours. The total weight of the pellets or beads in 600 ml of xylene was approximately 2 g. After boiling for 5 hours, the mesh bag was removed, dried in a vacuum oven at 120°C for 2 hours, and then weighed. The results were recorded as a percentage (%) based on the total weight of the material. The percentage of gel typically increases as the level of crosslinking increases.
[0177] (2) Foam density
[0178] The density of the foam beads was measured using the water displacement method according to ASTM D792. The results were recorded in grams (g) per cubic centimeter (g / cc or g / cm³).
[0179] (3) DMA test to characterize energy loss
[0180] -machinery and tools:
[0181] - RSA-G2, TA Instruments
[0182] - Geometric shape: Compression fixture, 15 mm disc
[0183] -method
[0184] - Frequency sweeping
[0185] - Frequency 0.1 to 100 rad / s
[0186] - Temperature: 25℃
[0187] - Strain: 10%
[0188] For each foamed bead example, three specimens were tested and the average value at each frequency was used.
[0189] Results and Discussion
[0190] (1) Foaming properties and bead characteristics
[0191] Bead foam examples were prepared from micro-pellets of INFUSE™ D9130.05 silane-grafted to various silane grafting levels as shown in Table 2. Crosslinking (XL) was performed before (pre-) and after (post-) foaming. 'Pre-' means XLing the silane-grafted pellets by immersing them in a catalyst and curing them at RT (or immersing them in hot water for curing), and then foaming the XL pellets into beads. 'Post-' means foaming the silane-grafted pellets into beads first, and then immersing the obtained beads with a catalyst and curing them at RT.
[0192] Table 2 provides the foaming temperature as well as the density and gel content of the final foamed beads. The foaming temperature is related to the polymer Tm, molecular weight, and XL degree (i.e., gel content). If the temperature is too low, the polymer viscosity will be too high, and consequently, the expansion ratio will be too low or even non-expansion. If the temperature is too high, the pellets (non-XL or low gel content) may stick together due to the melting of the polymer's crystalline phase, failing to form freely flowing beads. However, for sufficient XL pellets (i.e., relatively high gel content), a relatively high foaming temperature will be required to overcome the high melt strength induced by XL and obtain a high expansion ratio. As can be seen in Table 2, relatively higher foaming temperatures were required for pre-XL pellets compared to non-XL pellets to achieve similar bead densities. Higher gel content in the pellets required higher foaming temperatures. This can be explained by the high viscosity / melt strength caused by pre-XL. In the case of the original INFUSE™ D9130.05 pellets (CE1), it was found that it was difficult to reach a bead density of less than 0.17 g / cc. In this sense, silane grafting (reduction of MI due to specific chain coupling) and pre-XL improved the foaming properties of the pellets.
[0193] [Table 2]
[0194]
[0195] All other XLs were performed by immersing the catalyst in pellets or bead foams at room temperature.
[0196] The tanδ (i.e., energy loss) of foamed beads during compression was characterized using the DMA test. A low tanδ indicates low energy loss and good elasticity. Good elasticity and low energy loss are very important in bead-filled applications.
[0197] As shown in Table 3, the same silane-grafted (1.08% grafting ratio) pellets were prepared into different foam beads: CE7, non-XL, gel content 1.4%; CE8, post-XL, gel content 100%; IE9, pre-XL, gel content 95.5%. These examples had very similar foam densities. Their DMA result tanδs at typical frequencies of 0.1, 1.0, and 10 rad / s are provided in Table 3. The tanδ curves during frequency sweeping (0.1 to 10 rad / s) are shown in Figure 1, where more tanδ values are available for further comparison.
[0198] Clearly, XL (pre- or post-) beads had lower tanδ than non-XL beads (CE7 and CE1), which is consistent with the common understanding that XL can reduce energy loss in POE foams. However, what was surprising was that the pre-XL beads (IE9) had significantly lower tanδ than the post-XL beads (CE8) (despite the post-XL beads having a slightly higher gel content). IE10 used the same 1.08% silane-grafted pellets and produced relatively dense foam beads. Still, the tanδ was significantly lower than that of the post-XL CE8. These results demonstrated that the pre-XL approach can significantly improve the elasticity of foam beads compared to the post-XL approach.
[0199] In CE11 and CE13, much higher silane-grafted micropellets were foamed into beads and then post-XL. The resulting gel content was also 100%, but the crosslinking density must certainly be higher than that of CE8 and IE9 because the catalyst DBTDL can catalyze the XL of almost all silanes within a sufficient time. It is generally well known that higher crosslinking density leads to better elasticity. However, IE9 and IE10 still had lower tanδ than CE11 and CE13, which further demonstrated the elasticity improvement effect of pre-XL (compared to post-XL). The foam densities of some examples were not very close. The foam densities within the study range had a negligible effect on tanδ, as discussed below.
[0200] [Table 3]
[0201]
[0202] Although pre-XL led to an effective reduction in tanδ, the examples in Table 4 further indicated that a relatively high gel content is required. Generally, tanδ decreases as gel content increases. However, the change is not linear. As observed in CE2, CE3, and CE6, no significant decrease in tanδ was observed even with a large increase in gel content. However, in the case of IE9, which has a higher gel content (95.5%), a much lower tanδ was achieved. Therefore, it is considered that a sufficiently high gel content is important to obtain a very low tanδ, i.e., excellent elasticity.
[0203] [Table 4]
[0204]
[0205] In some of the above examples, a comparison of tanδ was performed between foamed beads of different densities. It is important to understand whether bead density itself is a significant factor influencing tanδ and to separate it from other factors (pre-XL vs. post-XL, gel content). In Table 5, three sets of examples were studied in which the silane grafting ratio, XL method, and gel content were identical for each set of examples. No significantly different tanδs were found in the examples of each set, indicating that bead density in this range (about 0.07 to 0.17 g / cc) is not a major factor influencing tanδ.
[0206] [Table 5]
[0207]
[0208] (2) Shape of foam beads
[0209] Figure 2 illustrates the cell morphology of the foam beads. The cell sizes of these samples were equivalent. All foams had a uniform cell size of less than 100 microns.
[0210] In summary, highly cross-linked polyolefin copolymer (OBC) bead foams have significantly better elasticity than non-XL foams. Pre-XL enables the production of foamed beads with significantly improved elasticity compared to those produced through the post-XL approach. The preferred gel content is 80% or more, more preferably 90% or more. These highly cross-linked bead foams are promising for bead-filling applications.
Claims
Claim 1 Foam beads formed from a composition comprising one or more polyolefin copolymers, wherein the gel content is 80% or more, the tanδ at 1 rad / s is 0.11 or less, and 70 wt% or more of the one or more polyolefin copolymers is silane-grafted. Claim 2 In claim 1, the foam beads comprising one or more types of polyolefin copolymers, wherein the polyolefin copolymer comprises a polyolefin elastomer. Claim 3 In claim 1, the silane-grafted polyolefin copolymer is a foamed bead having a silane grafting ratio of more than 0.3 wt% based on the total weight of the silane-grafted polyolefin copolymer. Claim 4 In claim 1, foam beads formed from the composition by crosslinking the pellets of the composition before foaming the pellets of the composition. Claim 5 A method for manufacturing foam beads according to any one of claims 1 to 4, comprising: (a) providing a composition comprising one or more polyolefin copolymers; (b) pelletizing the composition to form pellets; (c) crosslinking the pellets to a gel content of 80% or more; and (d) foaming the crosslinked pellets into foam beads, wherein the foam beads have a tanδ of 0.11 or less at 1 rad / s. Claim 6 A method according to claim 5, wherein the silane-grafted polyolefin copolymer has a silane grafting ratio of more than 0.3 wt% based on the total weight of the silane-grafted polyolefin copolymer. Claim 7 A method according to claim 5, wherein the one or more polyolefin copolymers are selected from the group consisting of one or more ethylene / α-olefin multiblock copolymers, one or more ethylene / α-olefin random copolymers, and any combination thereof. Claim 8 In claim 5, the method wherein one or more polyolefin copolymers have a melt index (MI) of 0.1 g / 10 min to 30 g / 10 min. Claim 9 delete Claim 10 delete Claim 11 delete Claim 12 delete Claim 13 delete Claim 14 delete
Citation Information
Patent Citations
Cross-linked foam structures of polyolefins and process for manufacturing
US5883145A
Olefin thermoplastic elastomer foam particles
KR1020200026192A